Preserving Local Literary Community: Literary Planning and Policy as a Cultural Strategy in Indonesia - Nadya Afdholy; Anas Ahmadi; Ghanesya Hari Murti (Universitas Muhammadiyah Malang, 2020)
The development of literary communities in Indonesia which spread in every region receive less attention from the government. Literary communities can continue to productively produce works but struggle to survive. This article aims to providing recommendations related to planning and policy to overcome various kinds of Indonesian literary, especially problems in international arena, regional potentials, literary contests, or historiographic documentation of Indonesian literary works development. Literary communities should be optimally empowered through macro planning and policy to revitalize their self in each region. The author recommends several strategies to revitalize local literary communities, namely forming special institutions from independent governments, noting and archiving the development of the literary community from year to year, and setting aside grants for the literary community in each region. This recommendation is expected to overcome the problem of Indonesian literature in international arena.